2020
DOI: 10.4103/jips.jips_368_19
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the attachments used in implant-supported overdentures

Abstract: Aim: To evaluate the survival rate, tissue response, and patient satisfaction of different attachments used in implant overdenture. Settings and Design: Systematic Review and Meta-analysis. Materials and Methods: Electronic search of peer-review articles published between 2001 and 2019 assessing the attachments used for implant-supported overdentures was done according to PRISMA Guidelies. The review evaluated sixteen articles related to surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…One study reported 34 prosthetic complications and a locator housing requiring 16 replacements [ 8 , 15 ]. To avoid complications, locator attachments require periodic repair and higher maintenance [ 24 ]. Recently, researchers invented a double-crown attachment option for locator attachments have that connects dentures to prepared teeth [ 25 ].…”
Section: Effects Of Attachment Types On Implant Overdenturementioning
confidence: 99%
See 3 more Smart Citations
“…One study reported 34 prosthetic complications and a locator housing requiring 16 replacements [ 8 , 15 ]. To avoid complications, locator attachments require periodic repair and higher maintenance [ 24 ]. Recently, researchers invented a double-crown attachment option for locator attachments have that connects dentures to prepared teeth [ 25 ].…”
Section: Effects Of Attachment Types On Implant Overdenturementioning
confidence: 99%
“…Overdenture attachments present very high survival rates. One study reported survival rates ranging from 96% to 97% for bar attachments, 96% to 100% for ball attachments, 90% to 92% for magnets, and 97% for locators with a mean follow-up period of 3 years [ 24 ]. Other studies have reported a 94% five-year survival rate for the bar attachment [ 28 ]; 89% and 93% survival rates for the bar and locator, respectively; [ 29 ], and 98% and 97% survival rates for the bar and the locator, respectively [ 30 ].…”
Section: Effects Of Attachment Types On Implant Overdenturementioning
confidence: 99%
See 2 more Smart Citations
“…The clinician on average, spent about 15 minutes more adjusting conventional dentures [18]. The patient should not be encouraged to accept a fixed prosthesis if a removable prosthesis can predictably satisfy a patient's needs and desires [21].…”
Section: Contraindicationsmentioning
confidence: 99%